When and Where Did They Strand? The Spatio-Temporal Hotspot Patterns of Cetacean Stranding Events in Indonesia - Putu Liza Kusuma Mustika; Kathryn K. High; Mochamad Iqbal Herwata Putra; Achmad Sahri; I Made Jaya Ratha; Muhammad Offal Prinanda; Firdaus Agung; Februanty S. Purnomo; Danielle Kreb (Oceans, 2022)
Analyses of the spatial and temporal patterns of 26 years of stranding events (1995–2011 and 2012–2021, n = 568) in Indonesia were conducted to improve the country’s stranding response. The Emerging Hot Spot Analysis was used to obtain the spatial and temporal hotspot patterns. A total of 92.4% events were single stranding, while the remaining were of mass stranding events. More stranding events were recorded between 2012 and 2021 in more dispersed locations compared to the previous period. Within the constraints of our sampling limitations, East Kalimantan and Bali were single stranding hotspots and consecutive hotspots. East Java and Sabu-Raijua in East Nusa Tenggara were mass stranding hotspots. Temporally, Raja Ampat (West Papua) experienced a significant increase in case numbers. The presence of active NGOs, individuals or government agencies in some locations might have inflated the numbers of reported cases compared to areas with less active institutions and/or individuals. However, our results still give a good understanding of the progression of Indonesia’s stranding responses and good guidance of resource allocation for the stranding network. Several locations in Indonesia that need more efforts (e.g., more training workshops on rescue and necropsies) have been identified in this paper. Suggestions to improve data collection (including georeferencing tips) have also been included.